Analysis of E-Commerce Adoption by Micro, Small, and Medium Enterprises (MSMEs) in Responding to Global Competition - Tulus Widjajanto (Yayasan Meira Visi Persada, 2026)
This study analyzes e-commerce adoption by Micro, Small, and Medium Enterprises (MSMEs) in facing global competition. The research method uses a quantitative approach with surveys of 250 MSMEs in Indonesia. The results show that 67% of MSMEs have adopted e-commerce platforms, with an average sales growth rate of 45% after adoption. The main factors influencing adoption include ease of platform use (85%), access to broader markets (78%), and technology support (72%). The main barriers are limited human resources (62%) and technology infrastructure (58%). This research provides strategic recommendations to increase e-commerce adoption among Indonesian MSMEs.